2020
DOI: 10.1002/jgm.3131
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in LOC105377871 and CASC16 with breast cancer in the northwest Chinese Han population

Abstract: Background Breast cancer represents the cancer with the highest incidence and mortality among women in the world, and its pathogenesis is complex. Single nucleotide polymorphisms (SNPs) are one of the factors that influence the risk of breast cancer. The present study aimed to investigate the effects of LOC105377871 and CASC16 polymorphisms on the risk of breast cancer in the northwest Chinese Han population. Methods We selected 503 breast cancer patients and 503 healthy controls for the present study. Genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
(61 reference statements)
0
12
1
Order By: Relevance
“…are more extensive compared to those in the study reported by Sun et al . In addition, the OR (95% CI) in the study by Sun et al . approaches a near critical value; if the individual study increased the sample size, this might yield a significant association.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…are more extensive compared to those in the study reported by Sun et al . In addition, the OR (95% CI) in the study by Sun et al . approaches a near critical value; if the individual study increased the sample size, this might yield a significant association.…”
mentioning
confidence: 61%
“…and Long et al . are more extensive compared to those in the study reported by Sun et al . In addition, the OR (95% CI) in the study by Sun et al .…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…[ 31 , 32 ] Zou et al found that rs4784227 was associated with an increased risk of lymph node metastasis in individuals with breast cancer. [ 26 ] RS4784227 is enriched in FOXA1 and regulates the affinity between chromatin and FOXA1 on the distal regulatory elements, leading to changes in the ability of FOXA1 to bind DNA. The binding site of FOXA1 can form chromatin rings with the promoter of CASC16 gene, and alterations in FOXA1-binding DNA sequence will directly affect the expression of CASC16 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis and overall prognosis of BC are multifactorial and result from interaction between modifiable factors such as breastfeeding and oral contraceptive use and nonmodifiable factors such as age, early menarche, late menopause, ethnicity, and genetic aberrations [ 7 , 8 ]. Among the above-mentioned multiple factors, genetic factors were the major drivers in the genesis of BC [ 9 11 ]. BRCA1 and BRCA2 have proved to be the two classical susceptible genes in the BC hereditary [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%